PENGARUH PSYCHOLOGICAL SKILLS TRAINING TERHADAP PENINGKATAN MENTAL TOUGHNESS DAN RAIHAN PRESTASI ATLET ELIT DUATHLON DAN TRIATHLON INDONESIA - Wahyu Hidayat, - (2022)
Tujuan dari peneliti ini ialah untuk mengetahui pengaruh Psychological Skills Training (PST) terhadap mental toughness dan raihan prestasi atlet elit duathlon dan triathlon Indonesia. Metode penelitian ini ialah eksperimen dengan desain penelitian one grup pretest-post test. Penelitian ini menggunakan instrumen Mental Toughness Quessioner 48 (MTQ-48) dan simulasi duathlon dan triathlon. Populasi penelitian ini atlet Pelatnas duathlon dan triathlon Indonesia, dengan teknik total sampling digunakan untuk memilih seluruh atlet sebagai sampel sebanyak 10 atlet (7 atlet putra dan 3 atlet putri). Analisis data dalam penelitian ini menggunakan paired sample t-test. Hasil penelitian ini Psychological Skills Training memberikan pengaruh yang signifikan terhadap peningkatan mental toughness atlet elit duathlon dan triathlon Indonesia dengan nilai signifikansi 0,000. Hasil kedua menunjukan nilai signifikansi 0,005 Psychological Skills Training memberikan pengaruh yang signifikan terhadap peningkatan prestasi atlet elit duathlon dan triathlon Indonesia. Kesimpulan penelitian ini menunjukan Psychological Skills Training (PST) memiliki pengaruh terhadap peningkatan mental toughness atlet elit duathlon dan triathlon Indonesia. Serta Psychological Skills Training (PST) memberikan pengaruh terhadap peningkatan prestasi atlet elit duathlon dan triathlon Indonesia. Kata kunci : Psychological Skills Training, Mental Toughness, Raihan Prestasi, Duathlon, dan Triathlon. THE EFFECT OF PSYCHOLOGICAL SKILLS TRAINING ON IMPROVEMENT OF MENTAL TOUGHNESS AND ACHIEVEMENT OF INDONESIAN ELITE ATHLETES DUATHLON AND TRIATHLON Wahyu Hidayat 2022 ABSTRACT The purpose of this research is to determine the effect of Psychological Skills Training (PST) on mental toughness and achievement of elite athletes in duathlon and triathlon Indonesia. This research method is an experimental research design with one group pretest-post test. This study uses the Mental Toughness Questioner 48 (MTQ-48) instrument and simulations of duathlon and triathlon. The population of this research is athletes of Indonesian national duathlon and triathlon athletes, with a total sampling technique used to select all athletes as a sample of 10 athletes (7 male athletes and 3 female athletes). Data analysis in this study used paired sample t-test. The results of this study Psychological Skills Training has a significant effect on increasing the mental toughness of elite duathlon and triathlon athletes in Indonesia with a significance value of 0.000. The second result shows a significance value of 0.005 Psychological Skills Training has a significant effect on increasing the achievements of elite athletes in duathlon and triathlon Indonesia. The conclusion of this study shows that Psychological Skills Training (PST) has an effect on increasing the mental toughness of elite duathlon and triathlon athletes in Indonesia. And Psychological Skills Training (PST) has an effect on increasing the achievements of elite athletes in Indonesian duathlon and triathlon. Keyword : Psychological Skills Training, Mental Toughness, Achievement, Duathlon, and Triathlon.